Appearance Fault Diagnosis of a Transformer Based on Data Set Optimization and Heterogeneous Model Ensemble - Xuan, Yi; Fan, Libo; Tu, Yongwei; Sun, Zhiqing; Han, Rongjie; Jiang, Jian; Chen, Yifang; Lai, Yibo; Huang, Jiabin (Frontiers in Energy Research, 2022)
Prosumers refer to the integration of production and consumption. Due to the large number of access to distributed power sources, electric vehicles, etc., which have a certain impact on power transformers, increasing potential failures, transformers need to be monitored. In recent years, image recognition technology based on deep learning has been widely used in intelligent inspection image analysis. Aiming at the problem that the accuracy of appearance fault diagnosis in intelligent inspection image is limited by image quantity and quality, an image data set optimization method based on seamless cloning algorithm and image cleaning is proposed. Firstly, a sample generation method based on the seamless fusion algorithm is proposed, which seamlessly fuses the corroded texture of other power equipment into the transformer image to generate the rust transformer image. On this basis, an image quality evaluation and screening method based on the XGBoost algorithm is proposed to evaluate the image quality of the dataset and clean the low-quality images. In addition, aiming at the limitation of a single diagnosis algorithm, an appearance diagnosis method based on heterogeneous model ensemble learning is proposed. By constructing multiple different learning models and using a weighted voting strategy to fuse model outputs as final outputs, the accuracy of fault diagnosis is improved.